Risk Factors for Acute Respiratory Infections in Children Between 0 and 23 Months of Age in a Peri-Urban District in Pakistan: A Matched Case-Control Study - Fatima Mir; Shabina Ariff; Maria Bhura; Suhail Chanar; Apsara Ali Nathwani; Muhammad Jawwad; Amjad Hussain; Arjumand Rizvi; Muhammad Umer; Zahid Memon; Atif Habib; Sajid Bashir Soofi; et al. (Frontiers Media S.A., 2022)
Background: Acute respiratory infection (ARI) accounts for nearly 15% of all childhood mortality in South Asia, with children from rural areas at higher risk due to inaccessibility to healthcare facilities. We therefore aimed to identify risk factors associated with ARI in children under 2 years of age in rural Pakistan.Methods: A retrospective 1:2 matched case-control study was conducted between October and December 2018 in Taluka Kotri, Jamshoro District of Pakistan. Cases were identified as children between 0 and 23 months of age with a history of fever, cough, sore throat, fast breathing, difficulty breathing, or chest indrawing in the 2 weeks prior to the survey. Controls were participants without symptoms of ARI, matched based on age in months. Data analysis was conducted using STATA version 15. Univariate and multivariable conditional logistic regression analyses were used to identify factors associated with ARI, and p < 0.05 was considered statistically significant.Results: We identified 1,071 cases of ARI who were matched with 2,142 controls. Multivariable analysis revealed that female gender [odds ratio (OR) 0.78, 95% confidence interval (CI): 0.67-0.91], exclusive breastfeeding (OR 0.81, 95% CI: 0.69-0.97), and comorbidity with diarrhea (OR: 1.64, 95% CI: 1.40-1.91) were significantly associated with ARI.Conclusion: Pakistan continues to progress toward reducing childhood mortality, particularly ARI-related deaths, for which it bears a great burden. This study identifies risk factors such as the male gender, breastfeeding, and comorbidities with diarrhea, which could open grounds for further programmatic implications in targeting a multifaceted approach to reducing incidences of ARI in rural areas of the country.